History Erased - Wayne A. Wiegand (The International Journal of Information, Diversity, & Inclusion, 2025)
Library science historian, Dr. Wayne A. Wiegand, examines the profession’s longstanding failure to acknowledge or address racism within its institutions and history. Despite the American Library Association’s 1939 Library Bill of Rights asserting commitments to intellectual freedom and non-discrimination, the library and information science (LIS) community has remained silent during pivotal moments of racial injustice, including the Alexandria Library sit-in, the aftermath of Brown v. Board of Education, and the targeting of Black librarians like Autherine Lucy and Ernestine Denham Talbert. Wiegand details how this silence extended into professional literature and conferences, leaving segregated libraries and acts of racial violence unexamined. Wiegand argues that librarianship’s culture of “politeness” and avoidance has led to collective historical amnesia, perpetuating myths of an unblemished profession. He calls for libraries to reckon with this erased history, integrate it into collective memory, and confront the ongoing implications of systemic racism.